The application of integrated remotely sensed and geographic data to facilitate rangeland mapping and condition assessment in the Ceres Karoo region of Southern Africa - MacKay, Craig (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.